Modelo simplificado de simulação de reservatórios: regressões dos volumes evaporado, vertido e regularizado - Ponte, Vitor Moreira da Rocha (2008)
The present research identifies simplified equations capable to determine the behavior of reservoirs. It considers four independent variables: i) coefficient of variation of annual inflow; ii) dimensionless reservoir capacity; iii) dimensionless evaporation factor, function of the average annual inflow, reservoir shape coefficients and potential net evaporation; and iv) probability of failure. The dependents variables are: i) dimensionless evaporation loss volume; ii) dimensionless spill loss volume; and iii) dimensionless release volume. Initially, were used data from reservoirs generated randomly. The reservoirs dependents and independents variables values were determined after its simulation. It was used linear regression to determine the relationship between the dependents and independents variables. Limits of validity and errors were also determined. The equations determined in this research were used in seventy-five reservoirs located in the state of Paraíba, Brazil, in order to validate them. By using the equations determined in this research, it is possible to identify: i) the behavior of reservoirs; and ii) the individual effect of each independent variable in the reservoir dependents variables. The equations developed in this thesis are easy to apply, time saving and have acceptable errors.